1995
DOI: 10.1016/s0741-5214(95)70224-5
|View full text |Cite
|
Sign up to set email alerts
|

The significance of microemboli detection by means of transcranial Doppler ultrasonography monitoring in carotid endarterectomy

Abstract: During CEA the presence of microembolism (> 10 microemboli) during dissection shows a statistically significant relationship with perioperative cerebral complications and with new ischemic lesions on magnetic resonance images of the brain. Moreover, microembolism during shunting is also related to intraoperative complications. Surgeons can be guided by the audio Doppler and emboli signals by changing their technique. This change may result in a decrease of microembolism and consequently in a decline of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(82 citation statements)
references
References 16 publications
0
78
1
3
Order By: Relevance
“…34 Several studies have found that the occurrence of postoperative cerebral ischemia is correlated with increased numbers of sonographic microemboli. 8,10,11 Given the small sample size of the present study and the relatively low rate of observed microemboli, our results do not allow any conclusion concerning the number of sonographic embolic signals and the occurrence of radiologically detectable cerebral lesions.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…34 Several studies have found that the occurrence of postoperative cerebral ischemia is correlated with increased numbers of sonographic microemboli. 8,10,11 Given the small sample size of the present study and the relatively low rate of observed microemboli, our results do not allow any conclusion concerning the number of sonographic embolic signals and the occurrence of radiologically detectable cerebral lesions.…”
Section: Discussioncontrasting
confidence: 67%
“…The rate of postoperative silent infarction was higher than in CT-based reports and ranged from 0% to 24%. 8,12,13,33 Still higher rates of silent ischemia would probably have been demonstrated in these MRI studies if they had been supplemented by diffusion-weighted sequences. In the present series, the probability of missing postoperative ischemic lesions was particularly small because DWI was performed in the first 24 hours after the operation to detect any short-lived cerebral changes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Presence of microemboli during carotid endarterectomy is an indicator of new ischemic events (Ackerstaff, Moons et al 2000) (Ackerstaff, Jansen et al 1995). Presence of microemboli should alert the physician to change the surgical technique.…”
Section: Monitoring During and After Carotid Endarterectomymentioning
confidence: 99%